FDG PET and MRI Findings in a Case of Bing-Neel Syndrome. (April 2018) - Bund, Caroline; Lhermitte, Benoît; De Seze, Jérôme; Kremer, Stéphane; Namer, Izzie-Jacques
Abstract : Abstract: A 64-year-old man was admitted for expressive aphasia with lack of words. He had been diagnosed with Waldenström 4 years before. At that time, he received 6 cycles of single-agent fludarabine, and remission was obtained. Because of acute expressive aphasia, he underwent brain MRI, which showed frontoparietal and insular subcortical gadolinium enhancement; Bing-Neel syndrome was suspected. Fronto-temporo-insular hypometabolism and left parietal hypometabolism were highlighted on FDG PET/CT. Structural and functional brain imaging revealed impairment of brain areas due to white matter changes and reinforced the diagnosis.